Efektifitas Reflective Learning Pada Sikap Profesional Mahasiswa Kebidanan - Andina Vita Sutanto; Mohammad Hakimi; Mubasysyir Hasanbasri (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Midwifery educational institutions have an important role in the scoring power of professional andqualified midwives. To be able to produce a professional midwife as expected, then it takes a model of effective andinnovative learning.Objective: To know the effectiveess of reflective learning on Student Academy Midwifery Yogyakarta.Method: This type of research survey with descriptive study. The research at Academy of Midwifery in Yogyakarta.Sample student research level I, II, and III. Sampling using a minimum sample size. Variable independent variable research, namely is the reflective learning. The dependent variable is the attitude of professional midwiferystudents.Result: The result showed statistical significance (P <0.05) between the independent variable (reflective learning)with the dependent variable (professional attitude) with a prevalence ratio 2.13 95% CI (1.62 to 2.78).Conclusion: Students who did reflective learning finely will have a chance to do a good professional attitude.Keywords: Reflective learning, professional attitude, midwifery student